Large-scale simulations of H and He reionization and heating driven by stars and more energetic sources. Issue 4 (11th September 2020) - Eide, Marius B; Ciardi, Benedetta; Graziani, Luca; Busch, Philipp; Feng, Yu; Di Matteo, Tiziana
ABSTRACT: We present simulations of cosmic reionization and reheating from z  = 18 to z  = 5, investigating the role of stars (emitting soft UV-photons), nuclear black holes (BHs, with power-law spectra), X-ray binaries (XRBs, with hard X-ray dominated spectra), and the supernova-associated thermal bremsstrahlung of the diffuse interstellar medium (ISM, with soft X-ray spectra). We post-process the hydrodynamical simulation MassiveBlack-II (MBII) with multifrequency ionizing radiative transfer. The source properties are directly derived from the physical environment of MBII, and our only real free parameter is the ionizing escape fraction f esc . We find that, among the models explored here, the one with an escape fraction that decreases with decreasing redshift yields results most in line with observations, such as of the neutral hydrogen fraction and the Thomson scattering optical depth. Stars are the main driver of hydrogen reionization and consequently of the thermal history of the intergalactic medium (IGM). We obtain 〈 x H ii 〉 = 0.99998 at z  = 6 for all source types, with volume-averaged temperatures $\langle \, T \rangle \sim 20\, 000$  K. BHs are rare and negligible to hydrogen reionization, but conversely they are the only sources that can fully ionize helium, increasing local temperatures by ∼10 4  K. The thermal and ionization state of the neutral and lowly ionized hydrogen differs significantly with different source combinations, with ISM and (to a lesser extent) XRBs, playing a significant role and, as a consequence, determining the transition from absorption to emission of the 21-cm signal from neutral hydrogen.